Comparison of airway management techniques for different access in a simulated motor vehicle entrapment scenario. (August 2016) - Steinmann, Daniel; Ahne, Thomas; Heringhaus, Christian; Goebel, Ulrich
Abstract : Background: Emergency airway management can be particularly challenging in patients entrapped in crashed cars because of limited access. The aim of this study was to analyse the feasibility of four different airway devices in various standardized settings utilized by paramedics and emergency physicians. Methods: Twenty-five paramedics and 25 emergency physicians were asked to perform advanced airway management in a manikin entrapped in a car's left front seat, with access to the patient through the opened driver's door or access from the back seat. Available airway devices included Macintosh and Airtraq laryngoscopes, as well as laryngeal mask airway (LMA) Supreme and the Laryngeal Tube. The primary endpoints were successful placement, along with attempts needed to do so, and time for successful placement. The secondary endpoints included Cormack–Lehane grades and rating of the difficulty of the technique with the different devices. Results: The overall intubation and placement success rates were equal for the Macintosh and Airtraq laryngoscopes as well as the LMA Supreme and Laryngeal Tube, with access from the back seat being superior in terms of placement time and ease of use. Supraglottic airway devices required half of the placement time and were easier to use compared with endotracheal tubes (with placement times almost >30 s). Paramedics and emergency physicians achieved equal overall successful placement rates for all devices. Conclusion: Both scenarios of securing the airway seem suitable in this manikin study, with access from the back seat being superior. Although all airway devices were applicable by both groups, paramedics and emergency physicians, supraglottic device placement was faster and always possible at the first attempt. Therefore, the LMA Supreme and the Laryngeal Tube are attractive alternatives for airway management in this context if endotracheal tube placement fails. Furthermore, supraglottic device placement, while the patient is still in the vehicle, followed by a definitive airway once the patient is extricated would be a worthwhile alternative course of action.